Financial spillovers across countries: The case of Canada and the United States - Kimberly Beaton; Brigitte Desroches (Bank of Canada, 2011)
The authors investigate financial spillovers across countries with an emphasis on the effect of shocks to financial conditions in the United States on financial conditions and economic activity in Canada. These questions are addressed within a global vector autoregression model. The framework links individual country vector autoregression models in which the domestic variables are related to the country-specific foreign variables. The authors' results highlight the importance of financial variables in the transmission of shocks to real activity and financial conditions in the United States to Canada. First, they show that shocks to U.S. output are transmitted quickly to Canada, with important implications for financial conditions. Second, they show that the most important source of financial transmission between the United States and Canada is through shocks to U.S. equity prices. Financial transmission through movements in the quantity of U.S. credit is also important for Canada.
Keywords: E27; E32; F36; F40; 330; Business fluctuations and cycles; Economic models; Financial stability; International topics; Finanzmarkt; Schock; Ansteckungseffekt; Gesamtwirtschaftliche Produktion; USA; Kanada